Troubling nationhood in U.S. Latina literature : explorations of place and belonging - Socolovsky, Maya, 1973- (Rutgers University Press, 2013)
This book examines the ways that U.S. Latina literature challenges popular definitions of nationhood and national identity. It explores the works of Mexican American, Puerto Rican, and Cuban American writers Denise Chavez, Ana Castillo, Sandra Cisneros, Judith Ortiz Cofer, Esmeralda Santiago, and Himilce Novas to show how these texts argue for the legitimate belonging of Latino/as within U.S. borders and counter anti-immigration rhetoric.
Keywords: American literature -- Hispanic American authors -- History and criticism.; American literature -- Women authors -- History and criticism.; Hispanic American women -- Intellectual life.; Hispanic Americans in literature.; Belonging (Social psychology); Identity (Psychology) in literature.; National characteristics, Latin American, in literature.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique.; Écrits de femmes américains -- Histoire et critique.; Américaines d'origine latino-américaine -- Vie intellectuelle.; Américains d'origine latino-américaine dans la littérature.; Appartenance (Psychologie sociale); Identité (Psychologie) dans la littérature.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM -- American -- Hispanic American.; American literature -- Hispanic American authors; American literature -- Women authors; Hispanic American women -- Intellectual life; Hispanic Americans in literature; Identity (Psychology) in literature; National characteristics, Latin American, in literature; Criticism, interpretation, etc.